Ungkapan Larangan di Kanagarian Padang Laweh Kecamatan Sungai Tarab Kabupaten Tanah Datar - Ramadhani, Yopi; Abdurahman, Abdurahman; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to describe and analyze the shape, meaning, structure, function, category, and value education of an expression of folk handicratft in Kenagarian Padang Laweh Kecamatan Sungai Tarab Kabupaten Tanah Datar. The data of this study is the prohibition expression Minangkabau in Kenagarian Padang Laweh. Source of research data is the primary source of oral sources as spoken by the informant as the original speakers. Data was collected using the methods and techniques refer to the record and advanced engineering techniques as noted. The findings of the study include 8 things: (1) transcription in Kenagarian Padang Laweh prohibition expression into Indonesian, (2) the shape of prohibilition expression, (3) meaning of prohibilition expression, (4) structure of prohibilition expression, (5) function of prohibilition expression, (6) category of prohibilition expression, (7) value education of prohibilition expression.